Literatur Review Strategi Mengidentifikasi Tahapan dan Dampak Konflik Terhadap Organisasi - Ika Nurhoikhatul Janah; Siti Nurhalimatul Fatihah; Immatul Adimah; Nurul Holisin; Dwi Erik Bidayanto (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This article is a literature review study. This research uses a literature review study where all information is obtained from articles and books. The results of this literature review research show that there are several stages and impacts of conflict in organizations. The stages of conflict in an organization can be identified, namely starting from conflict that is still hidden, conflict that precedes, conflict that can occur, conflict that is visible in behavior, resolution or conflict pressure and the consequences of conflict resolution. The impact of conflict has positive and negative impacts, where these impacts can be seen in how an organization or company can use conflict well.